The Success of the Population Administration Service Program Through the e-PAK LADI Kiosk in Pasuruan Regency - Shenia Agustin; Lailul Mursyidah (Indonesian Journal of Public Policy Review, 2022)
This study aims to analyze and describe the effectiveness of population administration services through the e-PAK LADI Kiosk in Jatiarjo Village, Prigen District, Pasuruan Regency. This research is a qualitative descriptive study using purposive sampling informant determination technique. Techniques for collecting data are interviews, observations, documentation and literature studies. The data analysis technique uses Miles and Huberman which consists of four components, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that there is a need for an increase in the number of service operators, a positive response from the community towards the e-PAK LADI Kiosk service, an increase in the number of issuance of documents such as KK, KIA and others without any fees to the community. And there are facilities and infrastructure that support the service activities of the e-PAK LADI Kiosk such as printing, paper drives, wifi and so on.